2021
DOI: 10.3390/life11030218
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Clinical and Ultrasound Enthesitis Scores in Ankylosing Spondylitis

Abstract: Introduction: Ankylosing spondylitis (AS) is a chronic inflammatory disease, part of the spondyloarthritis (SpA) group, characterized by axial (spine and sacroiliac joints), entheseal, and peripheral joint involvement, which is frequently associated with extra-articular manifestations. Material and Methods: The study included a number of 30 patients diagnosed with AS according to the New York modified criteria, with history of entheseal pain, hospitalized between 2016–2018 in the Department of Rheumatology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Studies evaluating the correlation of the US scores with CRP levels and ESR have shown variable results. Some studies have failed to show any correlation;[ 9 , 12 , 17 , 18 , 36 , 37 ] however, in agreement with our study, few studies have found a relationship between the US scores and CRP levels. [ 38 - 40 ] CRP is an objective marker of active disease in SpA, and a moderate correlation between the US scores and CRP levels may indicate the role of US score as a potential marker of active disease.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Studies evaluating the correlation of the US scores with CRP levels and ESR have shown variable results. Some studies have failed to show any correlation;[ 9 , 12 , 17 , 18 , 36 , 37 ] however, in agreement with our study, few studies have found a relationship between the US scores and CRP levels. [ 38 - 40 ] CRP is an objective marker of active disease in SpA, and a moderate correlation between the US scores and CRP levels may indicate the role of US score as a potential marker of active disease.…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies, both BUSES and lower extremity enthesis scores were found to be correlated with SPARCC. [ 16 , 17 ] Since the sonographic evaluation of axial entheses is relatively troublesome, it was wondered whether the ultrasonographic evaluation of peripheral entheses would be associated with a clinical axial enthesitis score. If the association was detected, only US peripheral evaluation might have been adequate to show also axial enthesitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 The use of US with PD helps differentiate between active and inactive inflammation within joints and periarticular soft tissues thus allowing more accurate and objective assessment. 15 Together the rheumatologist and radiologist should make the most of these developments in view of the recent recommendations from EULAR that offer helpful guidance. 16 …”
Section: Diagnostic Potential Of Imaging Modalities In Rheumatologymentioning
confidence: 99%